1991
DOI: 10.1126/science.1909457
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ -Induced Ca 2+ Release in Sea Urchin Egg Homogenates: Modulation by Cyclic ADP-Ribose

Abstract: Calcium-induced calcium release (CICR) may function widely in calcium-mediated cell signaling, but has been most thoroughly characterized in muscle cells. In a homogenate of sea urchin eggs, which display transients in the intracellular free calcium concentration ([Ca2+]i) during fertilization and anaphase, addition of Ca2+ triggered CICR. Ca2+ release was also induced by the CICR modulators ryanodine and caffeine. Responses to both Ca2+ and CICR modulators (but not Ca2+ release mediated by inositol 1,4,5-tris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
341
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 624 publications
(351 citation statements)
references
References 32 publications
6
341
1
1
Order By: Relevance
“…cADPR, NAADP, and ADPR are involved in the regulation of cellular Ca 2+ homeostasis. While cADPR and NAADP trigger Ca 2+ -release from intracellular stores [5][6][7], ADPR controls calcium entry through the plasma membrane channel TRPM2 [8,9]. It is difficult to envision how cADPR and NAADP can function inside the cell if they are generated by ectoenzymes.…”
Section: Introductionmentioning
confidence: 99%
“…cADPR, NAADP, and ADPR are involved in the regulation of cellular Ca 2+ homeostasis. While cADPR and NAADP trigger Ca 2+ -release from intracellular stores [5][6][7], ADPR controls calcium entry through the plasma membrane channel TRPM2 [8,9]. It is difficult to envision how cADPR and NAADP can function inside the cell if they are generated by ectoenzymes.…”
Section: Introductionmentioning
confidence: 99%
“…A product of NAD + metabolism, cADPR was discovered by Clapper et al [4] in extracts from sea urchin eggs and was shown to release Ca# + from intracellular stores distinct from the Ins(1,4,5)P $ -sensitive stores. cADPR has since been suggested as an endogenous ligand for the ryanodine receptor (RyR) [5]. In permeabilized rat parotid and lacrimal acinar cells, cADPR releases Ca# + from Ins(1,4,5)P $ -insensitive stores [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Effect of Cyclic ADP-ribose-Recent studies suggest that cyclic ADP-ribose (cADPr) is a second messenger capable of triggering intracellular Ca 2ϩ release in a variety of cell types (42,43). The cADPr-induced Ca 2ϩ release is thought to be mediated by ryanodine receptors and requires CaM (44,45).…”
Section: Activation and Inactivation Of The Cloned Ryr3mentioning
confidence: 99%